Early Combination of Albumin With Crystalloid Administration Might Reduce Mortality in Patients With Cardiogenic Shock: An Over 10-Year Intensive Care Survey - Zou, Zhi-ye; Wang, Bin; Peng, Wen-jun; Zhou, Zhi-peng; Huang, Jia-jia; Yang, Zhen-jia; Zhang, Jing-jing; Luan, Ying-yi; Cheng, Biao; Wu, Ming (Frontiers in Cardiovascular Medicine, 2022)
Background In updated international guidelines, combined albumin resuscitation is recommended for septic shock patients who receive large volumes of crystalloids, but minimal data exist on albumin use and the optimal timing in those with cardiogenic shock (CS). The objective of this study was to evaluate the relationship between resuscitation with a combination of albumin within 24 h and 30-day mortality in CS patients. Methods We screened patients with CS from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Multivariable Cox proportional hazards models and propensity score matching (PSM) were employed to explore associations between combined albumin resuscitation within 24 h and 30-day mortality in CS. Models adjusted for CS considered potential confounders. E-value analysis suggested for unmeasured confounding. Results We categorized 1,332 and 254 patients into crystalloid-only and early albumin combination groups, respectively. Patients who received the albumin combination had decreased 30-day and 60-day mortality (21.7 vs. 32.4% and 25.2 vs. 34.2%, respectively, P < 0.001), and the results were robust after PSM (21.3 vs. 44.7% and 24.9 vs. 47.0%, respectively, P < 0.001) and following E-value. Stratified analysis showed that only ≥ 60 years old patients benefited from administration early albumin. In the early albumin combination group, the hazard ratios (HRs) of different adjusted covariates remained significant (HRs of 0.45–0.64, P < 0.05). Subgroup analysis showed that resuscitation with combination albumin was significantly associated with reduced 30-day mortality in patients with maximum sequential organ failure assessment score≥10, with acute myocardial infarction, without an Impella or intra-aortic balloon pump, and with or without furosemide and mechanical ventilation (HRs of 0.49, 0.58, 0.65, 0.40, 0.65 and 0.48, respectively; P < 0.001). Conclusion This study found, compared with those given crystalloid-only, resuscitation with combination albumin within 24 h is associated with lower 30-day mortality of CS patients aged≥60. The results should be conducted to further assess in randomized controlled trials.